Echoes of Liberation: Mujibur Rahman’s Enduring Legacy in Bangladesh’s Contemporary Political Tapestry (Journal of Advanced Research in Social Sciences, 2025)
Sheikh Mujibur Rahman (1920–1975) played a pivotal role in shaping Bangladesh’s political landscape during its liberation movement. This paper examines the contested legacy of his political vision in the context of Bangladesh’s current political scenario. Mujib’s vision for modern Bangladesh is rooted in four core principles: nationalism, secularism, socialism, and democracy, which remain foundational values in the country’s Constitution, despite numerous challenges. The study explores how Mujib’s concept of Bengali nationalism has evolved over the last five decades amidst internal and external challenges, including communal, extremist, and ethnic tensions in the context of South Asian and global politics. In August 2024, a student-led uprising led to the fall of the Awami League government under Mujib’s daughter, Sheikh Hasina. This uprising sparked significant discontent among political activists in Bangladesh regarding Mujib’s legacy. However, this paper argues that underlying values shared by Mujib’s vision and the goals of the uprising, particularly a commitment to liberal political ideals, are evident. The objectives of the new regime seeking to “reconstitute” Bangladesh can be traced back to Mujib’s foundational vision of a modern nation. By analyzing the connection between Mujib’s legacy and contemporary political developments, the paper seeks to enhance the understanding of Bangladesh’s political trajectory. The study is based on content analysis of reliable primary and secondary texts, including statements by leaders of the July 2024 uprising. The primary aim is to explore the relevance of Mujib’s ideals in today’s political landscape and identify common aspects between his political vision and current trends in Bangladesh’s political environment.